VALUE FREE AND VALUE LADEN IN ISLAMIC VALUE-BASED MANAGEMENT RESEARCH: AN INTEGRATIVE STUDY OF THE PHILOSOPHY OF SCIENCE AND RESEARCH ETHICS - Anton Prasetyo; Ahmed Hassan Ebed Elsalam Albawab; Rizqi Adhyka Kusumawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The long-standing debate about whether science should be value-free or value-laden has resurfaced as scientific research is used as a basis for public decision-making and organizational policy. On the one hand, the positivist tradition envisions science as devoid of moral, political, and religious considerations. On the other hand, recent studies in the philosophy of science suggest that this image is too naive. Heather Douglas, for example, argues that the ideal of value-free science is inadequate and undesirable because scientific decisions always involve inductive risks and moral consequences that cannot be ignored, so non-epistemic values inevitably come into play at various stages of research (Douglas, 2000; Douglas, 2009). Helen Longino adds that scientific theories are underpinned by background assumptions imbued with values and ideologies, so objectivity is better understood as the result of critical practices within the scientific community rather than as the complete absence of values (Longino, 1996). In management research, particularly when it touches on business ethics, social responsibility, and sustainability, this value dimension is increasingly evident, while the literature on Islamic business ethics and Islamic work ethics (IWE) explicitly places monotheism, justice, trustworthiness, and maslahah as guiding principles for organizational behavior (Sofyan et al., 2024; Zaroni & Lestari, 2025; Sudirman et al., 2024). This article compiles an integrative literature review of these writings to propose a framework for responsible objectivity in Islamic value-based management research, namely scientific practices that maintain methodological rigor while honestly acknowledging and managing the role of Islamic values in an explicit and accountable manner.